Progressive Dyspnea in a 40-Year-Old Man Caused by Giant Mediastinal Thymolipoma - Mohammad Vaziri; Kamelia Rad (Case Reports in Surgery)
Thymolipomas are rare tumors of the anterior mediastinum containing both thymic stroma and an abundance of fat. We present a 40-year-old man with no underlying disease who presented with cough and progressive dyspnea. Clinical evaluation revealed a giant mass of lipid density filling almost the entire left hemithorax with mediastinal shift. Total excision of the 40 × 33 × 8 cm mass weighing 4 kg was performed via a left thoracotomy and the histopathologic diagnosis of the mass was reported as thymolipoma. The patient remains alive and disease-free, twelve months after the intervention.